The Royal household of Marie-Louise of Orleans, 1679–1689: The struggle over executive offices - Borgognoni, Ezequiel (2018)
Fil: Borgognoni, Ezequiel. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales; Argentina